Estrategias didácticas constructivistas para el logro de ambientes de aprendizaje participativos e incluyentes en la asignatura de Biología. Año lectivo 2022-2023 - Sizalima Arias, Evelyn Julissa (2023)
The constructivist didactic strategies look for the student have an active role in its learning and be the creator of its own knowledge, in this way its academic performance is strengthen. The purpose of the Curricular research is to enhance the academic performance of students in the subject of Biology of the first year of baccalaureate of “27 de febrero” High school, through the application of constructivist didactic strategies that promote the participation and inclusion of all students in the teaching and learning process. The development of the research has been carried out through the inductive methodology, since the problem is identified starting from particular research, reaching a general knowledge. Its approach is qualitative because of the way it analyzes and obtain data. According to the nature of the information, it corresponds to a participatory action research because it intervenes in the educational reality of the students, improving the detected problem, and it is of transversal type due to the time in which it was carried out. In addition, for the data collection, different instruments as well as research and evaluation were used. Among the most efficient strategies are: learning by experimentation, cooperative work, learning by discovery, flipped classroom, which allowed the improvement of academic performance, in such a way, it can be concluded that constructivist didactic strategies that promote the participation and inclusion, are a key factor at the time of improve the learning. Key words: constructivism, teaching-learning, learning outcomes, student participation.